Scientific capacity building and the ontologies of herbal medicine in Ghana. Issue 3 (1st September 2016) - Droney, Damien
Abstract: The Centre for Scientific Research into Plant Medicine, a large herbal medicine research center in Ghana, has received important research equipment and training through a transnational research collaboration involving the Japanese International Cooperation Agency. By situating this project in regional debates about traditional medicine research priorities and the ontologies of plant medicine, this article argues that the collaboration had the perceived effect of standardizing research practices oriented toward drug discovery rather than the rationalization of crude drug preparations. This shows that "capacity-building" components of research collaborations should not be taken as the transfer of neutral goods from one location to another. They are charged with the political potential to make crucial decisions about the objects of research in postcolonial Africa.